2009
DOI: 10.1111/j.1751-1097.2009.00548.x
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitized DNA Damage: The Case of Fluoroquinolones

Abstract: This review focuses on DNA damage photosensitized by the fluoroquinolone (FQ) antibacterial drugs. The in vivo evidence for photocarcinogenesis mediated by FQs is presented in the introduction. The different methods employed for detection of DNA-photodamage mediated by FQs are then summarized, including gel electrophoresis (with whole cells, with isolated DNA and with oligonucleotides) and chromatographic analysis (especially HPLC with electrochemical and MS ⁄ MS detection). The chemical mechanisms involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 52 publications
0
52
0
Order By: Relevance
“…An amplification of immuno-suppression by local enhancement of the inhibitory effect on immuno-competent cells has been shown for fluoroquinolones [21]. Concerning genotoxicity, it has been reported, in an experimental model, that fluoroquinolones, especially lomefloxacin and fleroxacin, associated with UVA radiation, enhanced tumor prevalence and drastically shortened the median latent period of tumor onset compared with UVA alone [2224]. In UV-irradiated xeroderma pigmentosum group A gene-deficient mice, defective in nucleotide excision repair, the treatment with lomefloxacin induced DNA damage [25].…”
Section: Discussionmentioning
confidence: 99%
“…An amplification of immuno-suppression by local enhancement of the inhibitory effect on immuno-competent cells has been shown for fluoroquinolones [21]. Concerning genotoxicity, it has been reported, in an experimental model, that fluoroquinolones, especially lomefloxacin and fleroxacin, associated with UVA radiation, enhanced tumor prevalence and drastically shortened the median latent period of tumor onset compared with UVA alone [2224]. In UV-irradiated xeroderma pigmentosum group A gene-deficient mice, defective in nucleotide excision repair, the treatment with lomefloxacin induced DNA damage [25].…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that the reaction of 1 O 2 (Type II ROS) leads to the specific formation of 8-oxoGua whereas Type I gives rise, among other degradation products, 8-oxoGua and 2,6-diamino-4-hydroxy-5-formamidopyrimidine (FapyGua), to the transient formation of the guanine radical cation (Gua •+ ) in DNA. In that respect, several detailed mechanistic studies have provided relevant information on the contribution of the oxidation mechanisms to the degradation of nucleosides and isolated DNA (174)(175)(176). Among fluoroquinolones (for recent reviews, see Lhiaubet-Vallet et al [175] and de Guidi et al [176]), lomefloxacin and, to a lesser extent, enoxacin act as predominant Type I photosensitizers whereas ofloxacin and norfloxacin react with DNA mainly through 1 O 2 oxidation (93).…”
Section: Oxidation Reactions Mediated By Photosensitizersmentioning
confidence: 99%
“…In that respect, several detailed mechanistic studies have provided relevant information on the contribution of the oxidation mechanisms to the degradation of nucleosides and isolated DNA (174)(175)(176). Among fluoroquinolones (for recent reviews, see Lhiaubet-Vallet et al [175] and de Guidi et al [176]), lomefloxacin and, to a lesser extent, enoxacin act as predominant Type I photosensitizers whereas ofloxacin and norfloxacin react with DNA mainly through 1 O 2 oxidation (93). It was subsequently confirmed that ofloxacin oxidized predominantly DNA mostly through the Type II mechanism (177) as also shown for norfloxacin (178).…”
Section: Oxidation Reactions Mediated By Photosensitizersmentioning
confidence: 99%
“…These two sensitizers exhibit an E triplet value of approximately 275 kJ mol À1 . [37] Finally, two compounds with lower E triplet values (< 270 kJ mol À1 ), flurbiprofen [38] (FP) and 4biphenylcarboxylic acid [11,39] (BPC), were included. Not only several sensitizers but also several natural DNAs were studied in order to determine the impact of the base composition (Table S1 in the Supporting Information) on the distribution of CPDs upon TTET.…”
Section: Introductionmentioning
confidence: 99%